A head‐to‐head comparison of three coronary fractional flow reserve measurement technologies: The fractional flow reserve‐device study. Issue 6 (12th August 2019) - Beygui, Farzin; Lemaître, Adrien; Bignon, Mathieu; Wain‐Hobson, Julien; Briet, Clément; Ardouin, Pierre; Sabatier, Remi; Parienti, Jean‐Jacques; Blanchart, Katrien; Roule, Vincent
Abstract: Objectives: To compare three FFR technologies: the electric‐sensor Pressurewire® (P), the optic‐sensor Comet® (C) guidewire, and the optic‐sensor Navvus® (N) microcatheter. Background: Different technologies are used to measure fractional flow reserve (FFR) for the functional assessment of coronary lesions with potential discrepancies. Methods: Sixty‐six FFR measurements performed on 32 lesions using each technology were used for a paired comparison of FFR on simultaneous measurements and in clinically relevant conditions (guidewires alone, N on a guidewire). Results: Simultaneous measurements of FFR were significantly ( p  < .0001) correlated between systems ( ρ = 0.88, 0.81 and 0.86 for P and N, P and C and, C and N, respectively). The presence of the N microcatheter, led to reduced values of FFR measured by P or C guidewires ( p  < .0001). The concomitant presence of P and C guidewires led to significantly lower FFR values ( p  < .0001) measured by P but not by C. In clinically relevant conditions, values of FFR measured by the optic‐sensor C guidewire and N catheter were similar and lower than those measured by the P guidewire ( p  < .0001). The agreement between the three technologies (FFR ≤ 0.80) was 94%. Conclusions: FFR values simultaneously measured by three different technologies, are strongly correlated, and provide strongly concordant results. However, significant differences are found between values of FFR. The presence of N, but also C lead to a decrease of FFR measured by P. In clinically relevant conditions, the two optic‐sensor technologies provide similar FFR measurements, lower than those measured by the piezo‐electric technology suggesting a sensor‐technology‐related measurement variability. Clinical trial registration: NCT#03052803.